A Block Corner-Occupying Heuristic Algorithm for Constrained Two-Dimensional Guillotine Cutting Problem of Rectangular Items - Weiping Pan (IEEE Access, 2019)
Aiming at the constrained two-dimensional guillotine cutting problem of rectangular items, a heuristic algorithm with block corner-occupying pattern is presented in this paper. It can maximize the pattern value for the totally included items, but the occurring frequency of each item type doesn’t exceed its upper bound. Several rows and columns of identical items are packed at the left-bottom corner of the sheet, and the remaining part is divided into two sub-sheets. The sub-sheets are then packed and divided in the same way till no items can be packed. This upper bound and normal size methods applied in the algorithm will avoid the unnecessary calculation. The algorithm is compared with 9 literature algorithms with benchmark instances and random instances. Computational results show that, compared with the 8 heuristic algorithms, the pattern value of this algorithm is increased by 0.787% to 6.119% and the calculation time is reasonable. Compared with the exact algorithm, for large size instances the pattern value of this algorithm is 0.090% lower than it, but the calculation time is only 0.079% of it.